2022
DOI: 10.1021/acs.chemmater.2c03066
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Second-Harmonic Generation of van der Waals CuInP2S6 via Pressure-Regulated Cationic Displacement

Abstract: Design and exploration of high-performance nonlinear optical (NLO) materials have long been sought with the goal of tunable local structures and NLO properties for advanced laser technology. Thus far, the design strategies for second-order NLO materials have been mainly focused on anionic groups that have made great progress in the development of new NLO compounds. However, few studies have focused on the effects of cationic components and their contributions to NLO properties have long been underappreciated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 56 publications
(85 reference statements)
0
18
0
Order By: Relevance
“…Previous studies 24,25 reported that CIPS maintains the ambient conditions phase up to 4-5 GPa then a phase transition from the monoclinic (Cc) to centrosymmetric trigonal (P-31m) structure occurs. However, the sharp increase in spontaneous polarization up to about 0.26 GPa has not been reported.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies 24,25 reported that CIPS maintains the ambient conditions phase up to 4-5 GPa then a phase transition from the monoclinic (Cc) to centrosymmetric trigonal (P-31m) structure occurs. However, the sharp increase in spontaneous polarization up to about 0.26 GPa has not been reported.…”
Section: Resultsmentioning
confidence: 97%
“…33 However, the increased optical band gap under high pressure indicates that the coupling is weakened, and the migration of Cu cations to the center of the S octahedron becomes the dominant factor. 25 The competition between the two factors likely give rise to the plateau of remanent polarization between 0.26 and 1.4 GPa.…”
Section: Discussionmentioning
confidence: 99%
“…25 The band gap obtained by the Tauc plot method is 2.8 eV (Figure 1d, inset), consistent with a previous result. 22 In situ high-pressure optoelectronic experiments were conducted on CIPS. The photoresponse was measured first at 0.6 GPa with different voltages and light power intensities.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It has been proved that the ferroelectric phase transition temperature T c of CIPS can be modulated by hydrostatic pressure. , In addition, a pressure-induced phase transition from monoclinic to trigonal has been demonstrated at 4.0 GPa . Recently, a remarkable enhancement of second-harmonic generation in CIPS has been realized by applying pressure, which is related to Cu cation movement during the phase transition . The significant pressure-tuning properties of CIPS inspire us that high pressure may provide a potential way to regulate its optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation